Predictive Value of Serum Lactate in Determining Mortality in Patients with Septic Shock Undergoing Surgery - SHAFQATULLAH,; ANJUM, INAYAT HUSAIN; BASHIR, MUHAMMAD TARIQ; ULLAH, FARHAT; LUTFULLAH,; CHEEMA, KAMRAN (Pakistan Journal of Medical & Health Sciences, 2026)
Background: Septic shock is a leading cause of death in the perioperative period and a significant problem in emergency surgery. Timely recognition of those at risk of death is crucial. Serum lactate is a valuable marker of tissue hypoperfusion and metabolic derangement, but its role in predicting mortality in surgical patients with septic shock needs to be explored. Objective: To evaluate the usefulness of serum lactate in predicting mortality in patients with septic shock who require surgery. Methods: This prospective observational study was carried out in the Department of General Surgery, Sughra Shafi Medical Complex Narowal between 1st January 2024 and 31st March 2025. Consecutively, 80 adult patients with septic shock who required surgery were included in the study. Lactate was measured at the time of admission and at 6 hours following resuscitation. Lactate clearance was determined, and outcomes were monitored until discharge or death. Statistical analysis was performed using SPSS-26. Results: The average age of the patients was 54.1±15.2 years, and 61.3% were men. In-hospital mortality was 35.0%. Admission serum lactate levels were significantly higher in non-survivors 5.9±1.5 mmol/L than in survivors 3.4±1.0 mmol/L. Lactate levels at 6 hours were also higher in non-survivors 5.0±1.3 mmol/L than survivors 2.5±0.8 mmol/). Lactate clearance was also significantly lower in non-survivors 10.8±6.3% than in survivors 26.7±9.4%. Lactate levels at admission of 4.0 mmol/L or greater were significantly associated with mortality (p < 0.001). Conclusion: Lactate is an important predictor of death in surgical patients with septic shock. High admission lactate, persistent hyperlactatemia and low lactate clearance are all predictors of poor outcome.